2018
DOI: 10.2174/1874210601812010012
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Schwannoma of the Submandibular Region

Abstract: Background:We herein described a rare case of schwannoma of the hypoglossal nerve in the submandibular region with diagnostic imaging and histopathological findings.Case Report:A 31-years-old woman has had a palpable firm, rubbery, freely mobile mass in the submandibular region. Of imaging, MR images showed homogeneous isointensity on T1-weighted imaging (T1-WI), heterogeneous hypointensity on T2-WI, heterogeneous hyperintensity on short T1 inversion recovery (STIR), and heterogeneous enhancement on contrast-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…Pleomorphic adenomas, which frequently present in the submandibular gland, have similar MRI image with Hypoglossal nerve schwannomas 14 . This suggested that the MRI ndings of hypoglossal nerve schwannomas were not speci c 15 . The patient was diagnosed preoperatively as a submandibular gland tumor base on the symptom and MRI ndings.…”
Section: Discussionmentioning
confidence: 96%
“…Pleomorphic adenomas, which frequently present in the submandibular gland, have similar MRI image with Hypoglossal nerve schwannomas 14 . This suggested that the MRI ndings of hypoglossal nerve schwannomas were not speci c 15 . The patient was diagnosed preoperatively as a submandibular gland tumor base on the symptom and MRI ndings.…”
Section: Discussionmentioning
confidence: 96%
“…Patients usually present with an insidious-onset gradually progressive swelling which may or may not be accompanied by paresthesia [ 17 ]. The most common presenting symptoms of Hyn-derived schwannoma included tongue deviation [ 18 ], headaches [ 19 ], vertigo and nausea [ 11 ]. Hypoglossal nerve palsy was the most frequent presenting sign, occurring in 80% of the cases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic tumours arise from the neural crest which differentiates into the Schwann cells and sympathicoblasts. 5 The Schwann cells give rise to neurofibroma and neurilemmoma (Schwannoma). 6 Schwannoma is a slow growing solitary and encapsulated tumour attached to a nerve.…”
Section: Discussionmentioning
confidence: 99%